Stressors related to transfers and coping strategies employed by female workers at ZIMRA - Maseko, Recent (Midlands State University, 2017)
ABSTRACT The study explored the stressors related to transfers and coping strategies employed by female workers at ZIMRA. It was based upon the problem statement that transferring an employee from one working area to another severely affected work-life balance of that employee. The ultimate purpose of the research being to make known all the stressors related to transfers and coping strategies used by employees so that stressors could be eliminated and coping strategies improved so as to promote employees’ well-being. The study was guided by the Transactional model of stress with attempt to show how employee transfers result in stress. A qualitative approach and phenomenological research design were used and to come up with sample, the researcher used convenient sampling whereas data saturation method was used to determine sample size. The research consisted of 14 female participants of which 12 were non-managerial and 2 were managerial employees. The data was collected through in-depth interviews was then coded, categorised and analysed using thematic data analysis. The major themes were work-life stressors related to transfers, coping strategies used by ZIMRA female workers to cope with stress. The conclusions drawn were that there are so many stressors related to transfers, these included family disintegration, homesickness, increased financial constraints and challenges in adapting and relearning new procedures. The study also found that emotion focused coping strategies were mostly used by employees especially seeking social support to cope with stress and the major recommendation most employees gave was that during transfers, the proximity between the new station and employees’ home and family should be maintained.